Perceived Poverty and Alleviation Efforts of Kogi State Community and Social Development Agencies in Kogi State: An Empirical Investigation - Jibo, Abubakar Ibrahim (Journal of Social Economics Research, 2020)
This study investigated the perceived poverty and alleviation efforts of Kogi State Community and Social Development Agencies in Kogi State, Nigeria. The study adopted survey research design. The survey was conducted on selected rural areas of Kogi State. Snowball sampling method (which involves referral of respondents) was used, and the total of 300 respondents was surveyed. The sampling procedure adopted for the study was simple random sampling. Data were analysed in tables using percentage and Ordered Probit Regression. Findings show that poor rural roads and inaccessible water supply significantly and negatively affect the socio-economic development of Kogi State; and that massive rural-urban drift and conducive educational environment created by private schools have positively contributed to the socio-economic development of Kogi State. Findings further show that coordinated management, commitment and discipline on the part of the members of the agencies have significant negative effect on the efforts towards poverty reduction in Kogi State; and that over-politicization, regular payment and monitoring logistics are seen to have significant positive effect on the efforts towards poverty reduction in Kogi State. The study recommended that the government and economic stakeholders should pay more attention to poor rural roads and inaccessible water supply as they significantly affect the socio-economic development of Kogi State. Also, the government should intervene in the procurement of alternative source of power supply and encourage increased number of private schools to complement effort on the socio-economic development process of Kogi State.